On the Mystery of Interpretation: Studia Humanitatis. Ars Hermeneutica. Metodologie A Theurgie Hermeneutické Interpretace IX. Kolektiv autorů. red.: Jan Vorel. Ostravská univerzita: Ostrava 2022., 148 p., ISBN: 978-80-7599-333-5 - Dohnal, Josef (Slavica, 2023)
The aim of this review is to introduce the ninth volume of the publication series Studia Humanitatis, Ars Hermeneutica, published by the Department of Slavonic Studies, Faculty of Arts, University of Ostrava in the Czech Republic. The monograph is an output of proceedingsfrom conferences which are regularly organized by this department. Attention to the art of interpretation and the related need to situate works of art in a complex web of cultural and historical connections is an important part of the effort to understand the deep context of artistic creation as such and the possibility for recipients to gain the most accurate understanding of the message conveyed by a work of art. The monograph highlights a number of aspects of artisticcreation: it notes the circumstances of the creation of the artwork, the ability of the interpreter to place the artwork in the context of the historical conditions in which it is created, and the theoretical concepts that can be used for its interpretation.